2014
DOI: 10.1007/s12185-014-1537-7
|View full text |Cite
|
Sign up to set email alerts
|

Cancer gene therapy using mesenchymal stem cells

Abstract: Cellular and gene therapies represent promising treatment strategies at the frontier of medicine. Hematopoietic stem cells, lymphocytes, and mesenchymal stem cells (MSCs) can all serve as sources of cells for use in such therapies. Strategies for gene therapy are often based on those of cell therapy, and it is anticipated that some examples will be put to practical use in the near future. Given their ability to support hematopoiesis, MSCs may be useful for the enhancement of stem cell engraftment, and the acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…An array of growth factors, including PDGF, insulin-like growth factor 1 (IGF1), HGF, EGF and VEGF, as well as chemokines, such as RANTES/CCL5, CCL22 and, to a lower extent, SDF-1/CXCL12 and their respective receptors, have been implicated in MSC migration (Ponte et al 2007, Spaeth et al 2008) and many of these have been shown in this and other studies to be regulated by thyroid hormones via differential gene expression and receptor crosstalk (Davis et al 2011, Hercbergs et al 2012. Modulation of recruitment and engraftment efficiency of MSCs is of clinical interest, in settings of tissue regeneration, in the context of general tumour growth and the emerging field of MSC-based gene delivery in cancer therapy (Knoop et al 2011, Knoop et al 2013, Uchibori et al 2014. As the tumour stroma plays such a key role in tumour growth, angiogenesis and metastatic potential, it has become an important target for tumour therapy.…”
Section: Discussionmentioning
confidence: 82%
“…An array of growth factors, including PDGF, insulin-like growth factor 1 (IGF1), HGF, EGF and VEGF, as well as chemokines, such as RANTES/CCL5, CCL22 and, to a lower extent, SDF-1/CXCL12 and their respective receptors, have been implicated in MSC migration (Ponte et al 2007, Spaeth et al 2008) and many of these have been shown in this and other studies to be regulated by thyroid hormones via differential gene expression and receptor crosstalk (Davis et al 2011, Hercbergs et al 2012. Modulation of recruitment and engraftment efficiency of MSCs is of clinical interest, in settings of tissue regeneration, in the context of general tumour growth and the emerging field of MSC-based gene delivery in cancer therapy (Knoop et al 2011, Knoop et al 2013, Uchibori et al 2014. As the tumour stroma plays such a key role in tumour growth, angiogenesis and metastatic potential, it has become an important target for tumour therapy.…”
Section: Discussionmentioning
confidence: 82%
“…In this way, more and more molecularly targeted drugs are being developed for cancer therapies around the world, including in Japan. 3) In addition, gene therapy [4][5][6][7] and immunotherapy [8][9][10][11] have been developed for hematological malignancies, suggesting that the number of the treatment options will increase in the near future.…”
Section: )mentioning
confidence: 99%
“…Other mechanisms exclusively found with MSCs are immunomodulation (26,27) gene delivery (28)(29)(30) and angiogenesis (31)(32)(33). …”
Section: Can Stem Cells Differentiate Into Neural Lineage?mentioning
confidence: 99%